Impact of the meanings of the verb močʹ on its ability to form past tense and perfective - Israeli, Alina (Neophilologica, 2025)
It has long been noted that močʹ – smočʹ ‘can, be able to, may’ is an unusual aspectual pair, yet močʹ has been commonly treated as having three meanings: alethic, deontic and epistemic. The article abandons this traditional treatment and identifies seven distinct meanings of the verb močʹ: internal ability, permissive, epistemic, warning, perceived right, permission to begin, and external possibility. Their distinctions are not only semantic but also prosodic and in their ability to have a past tense form and/or to form a perfective based on smočʹ.